A multi-objective chemical reaction optimisation algorithm for multi-objective travelling salesman problem. (23rd December 2014) - Bouzoubia, Samira; Layeb, Abdesslem; Chikhi, Salim
The multi-objective travelling salesman problem (MOTSP) is a well-known combinatorial optimisation problem that belongs to the class of NP-hard problems. The MOTSP plays an important role in computing theory and in many real life applications. Unfortunately, finding efficient MOTSP solutions is still a challenging problem. That is why several methods were proposed to deal with this problem. This paper proposes a new multi-objective chemical reaction optimisation (MOCRO) algorithm to solve MOTSP. To maintain the diversity of the solutions, MOCRO uses a non-dominated sorting procedure proposed in NSGA2. Two new variants of MOCRO are proposed to deal the MOTSP. The first is MOCRO based on amount of domination (MOCRO-Dom), while the second is MOCRO based on weighted sum (MOCRO-WS). The experimental results have shown the superior performance of MOCRO-Dom and MOCRO-WS compared to NSGA2. Moreover, a comparative study between MOCRO-Dom and MOCRO-WS and the impact of the major parameters on the performance has been investigated.